Feedback Inhibition Might Dominate the Accumulation Pattern of BR in the New Shoots of Tea Plants (Camellia sinensis) - Zhang, Hanghang; Yang, Dong; Wang, Peiqiang; Zhang, Xinfu; Ding, Zhaotang; Zhao, Lei (Frontiers in Genetics, 2022)
Brassinosteroid (BR), a kind of polyhydroxylated steroid hormone, plays an important role in physiological and biochemical processes in plants. Studies were mainly focused on BR signaling and its exogenous spraying to help enhancing crop yields. Few researches centered on the accumulation pattern of BR and its mechanism. Yet it is crucial to unlocking the mystery of the function of BR and its cross action with other hormones. Tea (Camellia sinensis (L.) O. Kuntze) is one of the important economic crops in some countries and the new shoots are the raw materials for processing into various tea products. Different concentrations of exogenous BR were reported to have different effects on growth and development. The new shoots of tea plant can thus be considered as a valuable research object to study the accumulation pattern of BR. Herein, the quantity of five BR components (brassinolide, 28-norbrassinolide, 28-homobrassinolide, castasterone, and 28-norcastasterone) in different tissues of tea plant, including buds (Bud), different maturity of leaves (L1, L2) and stems (S1, S2) were determined by UPLC-MS/MS. A total of 15 cDNA libraries of the same tissue with three repetitions for each were constructed and sequenced. The BR-accumulation pattern and genes expression pattern were combined together for weighted gene co-expression network analysis (WGCNA). BR-accumulation-relative genes were then screened out by two kinds of method, based on K.in value and BR biosynthetic pathway (ko00905), respectively. The result showed that photosynthesis related genes and CYP450 family genes were actively involved and might play important roles in BR accumulation and/or its accumulation pattern. Foremost, feedback inhibition was more likely to dominate the accumulation pattern of BR in the new shoots of tea plant. Moreover, three conserved miRNAs with their target transcriptional factors and target mRNAs had been figured out from negative correlation modules that might strongly linked to the BR-accumulation pattern. Our study provided an experimental basis for the role of BR in tea plant. The excavation of genes related to the accumulation pattern of BR provided the possibility of cross-action studies on the regulation of BR biosynthesis and the study between BR and other hormones.